Karakter Tokoh Aruna Dalam Novel Kilovegram Karya Mega Shofani (Kajian Psikologi Individual Alfred Adler) - Euis Zian Safitri; Mari’i; Mahmudi Efendi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
One of the problems that is often shown in the kilovegram novel is the body image of the main female character. This is consistent with the fact that [more than boys], adolescent girls have high anxiety about body image. The issue of adolescent girls and their bodies is always interesting to study because this is a global problem. The purpose of this study is to describe the character of Aruna in the novel Kilovegram by Mega Shofani using Alfred Adler's individual psychology study. This research is a qualitative research. The instrument of this research is the author himself and a note sheet by using literature study and reading techniques on the type of literary work in the form of the Kilovegram novel. Based on the formulation of the problem in the research, the results of this study describe the character of Aruna in the novel Kilovegram by Mega Shofani using Alfred Adler's individual psychology. Adler's theory of personality consists of six principles, namely the inferiority principle, the superior principle, the style of life principle, the creative self principle, and the fictional principle. goals principle), and the social interest principle. Aruna's character's low self- esteem principle begins when she realizes that she feels less than perfect because of her physical appearance, plus her friends who always insult Aruna. Aruna's feelings of inferiority are described when the man she likes, Raka, her best friend since childhood, turned away from her own cousin who is thin, smart and multitalented. Departing from Aruna's lifestyle, her courage and independence are able to make an impetus to move towards what she hopes for. Being strong is not easy, therefore Aruna adjusts her lifestyle in such a way by accepting the situation and so that she can move to always be in the front despite the humiliation she feels. The creative self that Aruna's character does in developing her experience is by registering for fashion shows at school even though it is included in category C. Category C is for students who are fertile, even though they are fat, Aruna has high creativity than at first Aruna was pessimistic with her decision but she still Sign up because there are many to consider